Ayurvedic soaps or Ayurvedic shower gels: Which is more effective? - Manju M, Prabha; Austin, Dr. Anoop; Prabhu, D. K. Srinivasa (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Bar soaps are traditionally been one of the most commonly used means of handsanitation, particularly since the advent of antimicrobial hand soaps. It has been demonstratedthat soaps that do not contain agents that are antimicrobial in nature are seldom effective indecreasing the bacterial population present on the skin. Shower gels are higher viscosityvariants of foam baths, often containing higher levels of active materials. Efficacy of herbalextracts and the extracts incorporated in formulations like soap and shower gel wereevaluated. Vipruthi oil with 3 herbal extract components, Lakshadi oil, Eladi oil andSandalwood oil were the extract formulations taken for antimicrobial efficacy testing. Theseextract formulations were individually tested for their efficacy against common pathogens andthe same were incorporated in soap and shower gel formulations. The efficacy against S.aureus, S. pneumoniae, S. epidermidis, P. aeruginosa and C. albicans culture were evaluatedby Zone of inhibition and Minimum inhibitory concentration test. Mean and standarddeviation were used for statistical analysis. The Extract component I was found to be effective(100 microlitre (µl)) showing clear ZOI and MIC of 0.1 milligram/millilitre (mg/ml) againstS. pneumoniae. The soap formulation with sandal and eladi oil was showing MIC of 0.5mg/ml against S. aureus whereas the body wash with sandal and eladi oil was inhibitory at2.5 mg/ml. Thus both soap and body wash formulations were found to be more or lesssimilarly effective against selected pathogens.